Processing and structural properties of random oriented lead lanthanum zirconate titanate thin films. (January 2015) - Araújo, E.B.; Nahime, B.O.; Melo, M.; Dinelli, F.; Tantussi, F.; Baschieri, P.; Fuso, F.; Allegrini, M.
Graphical abstract: Highlights: Pyrochlore phase crystallizes near the bottom film-electrode interface. PLZT films show a non-uniform microstrain and crystallite size in depth profile. Complex grainy structure leads to different elastic modulus at the nanoscale. Abstract: Polycrystalline lead lanthanum zirconate titanate (PLZT) thin films have been prepared by a polymeric chemical route to understand the mechanisms of phase transformations and map the microstructure and elastic properties at the nanoscale in these films. X-ray diffraction, atomic force microscopy (AFM) and ultrasonic force microscopy (UFM) have been used as investigative tools. On one side, PLZT films with mixed-phase show that the pyrochlore phase crystallizes predominantly in the bottom film-electrode interface while a pure perovskite phase crystallizes in top film surface. On the contrary, pyrochlore-free PLZT films show a non-uniform microstrain and crystallite size along the film thickness with a heterogeneous complex grainy structure leading to different elastic properties at nanoscale.